The Education System Portrayed in the Bhavabhūti’s Mālatīmādhava - Dutta, Dr. Jintu Moni (International Journal of Advanced Science and Technology, 2020)
The Mālatīmādhava is a best known prakaraṇa in ten acts. This prakaraṇa is composed by Bhavabhūti, an eminent dramatist of Sanskrit literature. The author has taken the theme of the Mālatīmādhava from the Bṛhatkathā. Here Bhavabhūti has portrayed the love-story of Mālatī , the heroine , daughter of a minister of the Padmāvatī and Mādhava , the hero and son of the minister of Vidarbha. He has made clever arrangement of the events leading to the union of Mālatī and Mādhava. With this main story Bhavabhūti skillfully interwoven the love story of Makaranda , friend of Mādhava and Madayantikā, sister of Nandana .He has shown excellent constructive skill in contriving a love marriage between Mālatī and Mādhava .Here Buddhist nun Kāmandakī has played significant role in uniting the hero and the heroine.